Sheep and goat marketing in Nyando Climate-Smart Villages of western Kenya: What do the farmers gain? - Muigai, Anne W.T.; Ojango, Julie M.K.; Audho, James O.; Oyieng, Edwin P.; Recha, John W.M.; Radeny, Maren A.O. (2018)
The Nyando Basin covering two counties of western Kenya, namely Kericho and Kisumu has been adversely affected by climate change. Prolonged droughts, followed by heavy and unpredictable rainfall that causes flooding has led to land denudation, crop and livestock losses (IPCC, 2007; Onyango et al., 2012; Kinyangi et al., 2015). To address the adverse effects of climate change, and improve incomes for smallholder farmers, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the International Livestock Research Institute (ILRI) introduced improved indigenous breeds of goats and sheep to farmers grouped into clusters within the Climate-Smart Villages (CSVs) (Ojango et al., 2016). The aim was to cross selected Galla goat and Red Maasai sheep with the small local East African breeds for resilience.